AN ISLAMIC APPRAISAL OF MINDING THE GAP - Khan, Faiz (Journal of religious ethics, 2008)
The neglect of psycho-spiritual needs of patients as they traverse the modern healthcare system has been a featured theme in medical literature over the past decade. This literature, which often highlights in-patient palliative care, as well as acute and critical care settings, influences practice guidelines and protocols of doctors and nurses. In this essay, I review some of the pertinent issues raised in the literature and examine the validity of placing an ethical perspective on this issue. I also compare Islamic theocentric perspectives with secular, non-theistic perspectives on restoring psycho-spiritual care for patients. I then develop a framework for pastoral intervention based on aspects of the Islamic tradition and elaborate this framework by addressing clinical contexts and cases. The essay is an exposition based upon a review of the modern medical literature, an analysis of some of the traditional Islamic written sources, and the observations of the investigator, a practicing physician and an American Muslim.